2017
DOI: 10.1016/j.numecd.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

CPT1A methylation is associated with plasma adiponectin

Abstract: Background and Aims Adiponectin, an adipose-secreted protein that has been linked to insulin sensitivity, plasma lipids, and inflammatory patterns, is an established biomarker for metabolic health. Despite clinical relevance and high heritability, the determinants of plasma adiponectin levels remain poorly understood. Methods and Results We conducted the first epigenome-wide cross-sectional study of adiponectin levels using methylation data on 368,051 cytosine-phosphate-guanine (CpG) sites in CD4+ T-cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Methylation at cg00574958 in the 5' region of CPT1A (carnitine palmitoyltransferase 1A), associated with WHRadjBMI and WCHTadjBMI in the current study, has been previously associated with a number of cardiometabolic traits, including BMI, obesity, central obesity, WC unadjusted for BMI, lipid levels, lipoproteins, blood pressure, T2D, and plasma adiponectin [11,12,16,43,53,[61][62][63][64]. Also, a recent study has shown that blood pressure is causally associated with methylation at this site and methylation at this CpG influences expression of CPT1A [43].…”
Section: Biological Interrogation Of Nearby Genes Implicate a Role In The Neuroendocrine Systemsupporting
confidence: 49%
“…Methylation at cg00574958 in the 5' region of CPT1A (carnitine palmitoyltransferase 1A), associated with WHRadjBMI and WCHTadjBMI in the current study, has been previously associated with a number of cardiometabolic traits, including BMI, obesity, central obesity, WC unadjusted for BMI, lipid levels, lipoproteins, blood pressure, T2D, and plasma adiponectin [11,12,16,43,53,[61][62][63][64]. Also, a recent study has shown that blood pressure is causally associated with methylation at this site and methylation at this CpG influences expression of CPT1A [43].…”
Section: Biological Interrogation Of Nearby Genes Implicate a Role In The Neuroendocrine Systemsupporting
confidence: 49%
“…Associations of CPT1A with anthropometric traits [ 32 , 38 ] and triglyceride levels [ 39 ] were directionally consistent with previous studies in blood. Other associations with cg00574958 in CPT1A have been identified in EWAS of fasting blood lipids [ 39 41 ], adiponectin [ 42 ], the metabolic syndrome[ 43 ], and cardiovascular disease (CVD) risk [ 44 ]. Using the BIOS QTL browser, we identified an eQTM in blood associated with cg00574958 in CPT1A , indicating that DNAm at this site was inversely associated with expression of a transcript in the same gene, in line with findings by Irvin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 (IL6), interleukin-2 soluble receptor alpha (IL2sRα), tumor necrosis factor (TNF)-α and monocyte chemoattractant protein-1 (MCP1) were measured using quantitative sandwich enzyme immunoassays (ELISA kit assays, R&D Systems Inc., Minneapolis, MN) as described in previous publications [ 18 , 19 ]. Adiponectin was measured using an ELISA kit from R&D Systems (Minneapolis, MN) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%